2020
DOI: 10.1016/j.heliyon.2020.e03823
|View full text |Cite
|
Sign up to set email alerts
|

Free convection of a suspension containing nano-encapsulated phase change material in a porous cavity; local thermal non-equilibrium model

Abstract: Due to the instinctive temperature-dependent heat capacity of the Nano-Encapsulated Phase Change Material (NEPCM), there is a growing interest in the potential applications of such materials in heat transfer. As such, steady-state natural convection in a porous enclosure saturated with nanofluid using NEPCMs has been investigated in this study. The cavity is assumed to have constant hot and cold temperatures at the left and right vertical boundaries, respectively, and fully insulated from the bottom and top wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In equation (A2), r c is estimated as the average density of the liquid and the solid phase of PCM, Ghalambaz et al [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In equation (A2), r c is estimated as the average density of the liquid and the solid phase of PCM, Ghalambaz et al [6].…”
Section: Discussionmentioning
confidence: 99%
“…Here, to present a formula of the overall heat capacity of the NEPCM particles, the latent heat of the change phase should be considered. Three formulas can be introduced of the latent heat of phase change, namely, rectangular, triangular or sine profiles as presented in [6] as: In equation (A5), T Mr is the small temperature interval where the fusion temperature T f occurs in its middle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the solid wall has significant influences on the overall heat transfer. The thermal nonequilibrium state within various engineering systems and valuable outcomes are found in the studies reported by References [22‐25].…”
Section: Introductionmentioning
confidence: 99%